Capres ‘Gemoy’: a Personal Branding Analysis on Prabowo Subianto for the 2024 Presidential Election - Boeky, Kendra Sophie Priskilla (MEDIASI Jurnal Kajian dan Terapan Media, Bahasa, Komunikasi, 2024)
The purpose of this study is to analyze the personal branding of the presidential candidate, Prabowo Subianto, for the 2024 presidential election that has been closely associated with the word ‘gemoy’. Gaining massive interest from Gen-Zs due to this label, this study would look further into Prabowo’s ’gemoy’ personal branding through a qualitative study with content analysis method using three aspects of personal branding: self-identification, political product, and positioning in Gerindra political party’s TikTok account. In this research it is found that Prabowo is branded to be more approachable, looking out for the younger generations also through his program, and gathering the votes of the supporter of the grass roots, and supporter of the current president of Indonesia.